Implantation dermoid of the palm: An unusual presentation - Sanjay Saraf (Wolters Kluwer Medknow Publications, 2012)
An unusual case of palmar implantation dermoid causing paresthesia in the fingers is reported. The tumor was successfully excised with relief of the symptoms. The report discusses important points regarding management of such tumors.